If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -2y = 0 Solving 11x + -2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 11x + -2y + 2y = 0 + 2y Combine like terms: -2y + 2y = 0 11x + 0 = 0 + 2y 11x = 0 + 2y Remove the zero: 11x = 2y Divide each side by '11'. x = 0.1818181818y Simplifying x = 0.1818181818y
| -16x-14= | | 7m-8=7-8m | | 18-6c=-18-4c | | 4x^2-3x-5=-4 | | 5x+3(2x-1)=4(3x+5)-8 | | -18+6z-6=10+8z | | 101+10x+9=180 | | -3(1+6r)=11115-r | | s=70-28 | | -7r=-8r+13 | | 4-6(x-2)=26-9x | | 2x-6=4x-8 | | 8-7g=-4g-7 | | (5a-2)(5a+2)=0 | | 3x=2(x+123456) | | -8s=5-9s | | x+139+x+59=180 | | y+7=-5y+8y-7 | | 800x-550=66 | | x^2+96=x^2 | | -5r-3=3-4r | | -8+3n=n+6 | | -3(m-25000)=2(100-m) | | -6+3t=t+10 | | 7.93x+23.79=47.58 | | -3m=-10-5m | | 6=3+w | | -b=-2b-4 | | 8x-200=-9+7x | | 10x+14+6+6x=180 | | 8y-9-3y+8=0 | | 6x+7-3x=4-5x |